EFFECT OF NIGELLA SATIVA (KALONJI) ON SERUM CHOLESTEROL OF ALBINO RATS - Dahri, Amir Hamzo; Chandio, Atta Muhammad; Rahoo, Ali Akbar; Memon, Rafique Ahmed (Journal of Ayub Medical College Abbottabad, 2005)
Background: The increased level of LDL-c in the serum has a high risk and the increased serum HDL-c level has a low risk for the development of atherosclerosis. The effect of Nigella Sativa on levels of cholesterol fractions were determined in this study on rats. Methods: 24 albino rats of 08 weeks age having equal number of males and females were kept at optimum atmospheric condition. The blood samples were taken at the start and different control and experimental diets were given for 20 weeks. The experimental diets were added with Nigella Sativa as 30 mg/kg body weight. The blood samples were taken at the end of study. The blood samples drawn at the start and end of the study were estimated for serum cholesterol. The results of control and experimental groups were compared. Results: Total serum cholesterol in the control group showed increase from 8.3±3.30 to 13.96±9.3 at 20 weeks. The serum HDL cholesterol showed increase from 44.4±6.12 to 80.45±5.95 level at 20 weeks. The serum LDL cholesterol showed increase from 8.3±3.30 to 13.96±9.3 at 20 weeks. The total serum cholesterol in experimental group was increased from 76.9±6.5 to 117.5± 6.65 at 20 weeks. The serum HDL cholesterol levels was increased from 41.7±4.9 to 83.42±5.92 at 20 weeks as compared with control group. The LDL cholesterol levels were decreased from 12.7±6.9 to 8.5±7.8 at 20 weeks. Conclusion: This study shows significant decrease in serum low density lipoprotein cholesterol level, and increase in serum high density lipoprotein cholesterol levels. Keyword: Nigella Sativa, Serum Cholesterol, Rats